2013
DOI: 10.6020/1679-9844/2707
|View full text |Cite
|
Sign up to set email alerts
|

Cognição E Atividade Física: A Relação Existente Entre Atenção E a Velocidade Perceptiva Em Idosas Praticantes E Não Praticantes De Atividade Física

Abstract: Resumo-O Presente estudo teve como objetivo avaliar a Atenção (AT) e Velocidade Perceptiva (FI) numa população idosa, praticante e não praticante de atividade física. Foram sujeitos da pesquisa 54 idosos do sexo feminino residentes na Cidade do Porto e pertencentes ao Centro de Investigação em Atividade Física, Esporte e Lazer (CIAFEL) da Faculdade de Desporto da Universidade do Porto. Os instrumentos para mensuração dos dados foram: os testes de Atenção Toulouse-Piéron (1982) e Figuras Idênticas de Thurstone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
1
2
0
1
Order By: Relevance
“…This response favors the practice of physical activity via Nintendo Wii® in seniors. Similar responses have been identified in previous studies 36,37 and reinforce the relevance of exercise, since attentional processing is higher in active seniors than in sedentary ones 38 .…”
Section: Discussionsupporting
confidence: 90%
“…This response favors the practice of physical activity via Nintendo Wii® in seniors. Similar responses have been identified in previous studies 36,37 and reinforce the relevance of exercise, since attentional processing is higher in active seniors than in sedentary ones 38 .…”
Section: Discussionsupporting
confidence: 90%
“…This improvement seems to be associated with the intervention to encourage participation in physical exercise program, which requires from the older adults: planning, adaptation to the new routine, attention, adherence and learning the practice to be followed. Similarly, in a comparative study, it was found that the daily practice of physical exercise and its constant processing of information about the training to be followed are indicative of a gradual reduction in the effects of physical aging, as well as a reduction in the attention and concentration difficulties of the older adults (Fechine et al., 2013). Associated with this intervention, other factors, such as stimulation and orientation for self‐control and knowledge of chronic disease, may have positively influenced the cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a comparative study, it was found that the daily practice of physical exercise and its constant processing of information about the training to be followed are indicative of a gradual reduction in the effects of physical aging, as well as a reduction in the attention and con-centration difficulties of the older adults (Fechine et al, 2013). Associ- after the intervention and showed positive results (Fonseca et al, 2016).…”
Section: Nutritional Statusmentioning
confidence: 97%
“…Considerando as hipóteses inicialmente aventadas, verificou-se uma diferença significativa da atenção entre o grupo de atletas e não atletas, sendo esta maior para o grupo de atletas, confirmando a hipótese formulada e reiterando aspetos já indicados na literatura sobre o tema (Bonilha et al, 2015;Cardoso et al, 2015;Fechine et al, 2015;Fernandes & Fernandes, 2015;García et al, 2011;Medina-Papst et al, 2016). A segunda hipótese, sobre o efeito de interação entre a idade e o grupo de atletas e não atletas, não foi confirmada, possivelmente pela margem restrita de idades na amostra em questão, não sendo uma amostra com representatividade suficiente neste quesito.…”
Section: Discussionunclassified